IL-2 Inhibition of Th17 Generation Rather Than Induction of Treg Cells Is Impaired in Primary Sjögren’s Syndrome Patients - Luo, Jing; Ming, Bingxia; Zhang, Cai; Deng, Xiaofei; Li, Pingfei; Wei, Zhengping; Xia, Yu; Jiang, Kan; Ye, Hong; Ma, Wanli; Liu, Zheng; Li, Huabin; et al. (Frontiers in Immunology, 2018)
Objective To investigate the role of IL-2 in the balance of Th17 and Tregs and elucidate the underlying mechanisms of enhanced Th17 differentiation in primary Sjögren’s syndrome (pSS) patients. Methods This study involved 31 pSS patients, 7 Sicca patients, and 31 healthy subjects. Th17 and Treg cells were determined by flow cytometry, and IL-17A was detected by immunohistochemistry. IL-2 and IL-6 levels were assessed by ELISA and qPCR. p-STAT5 and p-STAT3 in salivary glands (SGs) were evaluated by immunohistochemistry and flow cytometry. The binding of STAT5 and STAT3 to the Il17a gene locus was measured by chromatin immunoprecipitation. Results We found that the percentage of Th17 cells was increased in the periphery and SG of pSS patients when compared with healthy subjects, but the Treg cells was unchanged. Meanwhile, the IL-2 level was reduced, and the IL-6 and IL-17A level was increased in the plasma of pSS patients. The ratio of IL-2 and IL-6 level was also decreased and IL-2 level was negatively correlated with the level of IL-17A. The expression of Il6 and Il17a mRNA was significantly increased, whereas Foxp3, Tgfb1, Tnfa, and Ifng mRNA were comparable. Furthermore, the level of STAT5 phosphorylation (p-STAT5) was reduced and p-STAT3 was enhanced in the SGs and in peripheral CD4+ T cells of pSS patients. In vitro IL-2 treatment-induced STAT5 competed with STAT3 binding in human Il17a locus, leading to decreased Th17 differentiation, which was associated with the reduced transcription activation marker H3K4me3. Conclusion Our findings demonstrated a Treg-independent upregulation of Th17 generation in pSS, which is likely due to a lack of IL-2-mediated suppression of Th17 differentiation. This study identified a novel mechanism of IL-2-mediated immune suppression in pSS.